PENGHINDARAN PAJAK:ANALISA PENGARUH KOMITE AUDIT DAN KUALITAS AUDIT TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN FOOD AND BEVERAGE DI INDONESIA - Ismiati, Windi Ismiati; Mujiani, Sari Mujiani; Rianto, Rianto (FEB-UP Press, 2025)
One of the problems that remains a challenge in Indonesia's taxation system is the low ratio of tax revenue to gross domestic product. This low tax ratio not only reflects the limited capacity of the state to collect taxes but may also indicate the presence of loopholes for tax avoidance practices, particularly those carried out by business entities. This study aims to examine the influence of the Audit Committee and Audit Quality on Tax Avoidance in the food and beverage sector on the Indonesia Stock Exchange (IDX) during the period 2020–2023. The study population consisted of 95 food and beverage companies, with a purposive sampling method yielding a sample size of 49 companies and 196 data points. Data analysis was conducted using panel data regression analysis with the statistical software EViews. The results of the study indicate that the audit committee partially has a positive effect on tax avoidance, and audit quality partially has a positive effect on tax avoidance. Additionally, the audit committee and audit quality simultaneously have a positive effect on tax avoidance. Overall, this study concludes that the existence and quality of oversight structures in companies, whether through audit committees or external auditors, have not been fully effective in curbing tax avoidance practices. On the contrary, these structures are positively correlated with tax avoidance practices that are legal but aggressive.